Bioelectricity and biomagnetism as keys to realization of neurotechnology - Erwin, Erwin; Taer, Erman; Afrinal, Afrinal (Indonesian Physics Communication, 2025)
The importance of bioelectricity and biomagnetism in neurotechnology has been outlined in this study. There are three main processes in neurotechnology, namely: signal delivery, data storage and data processing. These neurotechnological processes require three essential things, namely measurements, tools and materials. This scientific study describes the form of signal delivery in neurotechnology, the form of data storage and the form of data processing. The measurement methods that can be applied have also been described along with the tools and materials. Bioelectricity plays a very important role in building neurotechnology. Meanwhile, biomagnetism is an important aspect that cannot be separated from the phenomenon of bioelectricity which also supports systems in neurotechnology. The phenomena of bioelectricity and biomagnetism in neurotechnology are described in this study along with measurement devices and materials. Measuring devices and materials must be modified as conditions permit in their working conditions. It has also been studied that natural neurotechnological data storage in living creatures is through muscle memory, signal delivery occurs in the form of bioelectricity and data processing is a combination of data delivery and storage. This study also examines the future prospects of neurotechnology along with its moral aspects.